Creating and sustaining effective K-12 school partnerships : firsthand accounts of promising practices - Washington, Ahmad R.; Goings, Ramon G.; Henfield, Malik S. (Emerald Publishing Limited : Information Age Publishing, Inc., 2019)
"Although teachers, school counselors, and administrators are all situated within educational settings tasked with supporting students' educational development, rarely do these professionals have sufficient opportunities to learn from and collaborate with one another before entering these schools. Unfortunately, many of these professionals are unaware of the primary and secondary responsibilities their peers and colleagues assume. What's worse, this lack of insight potentially compromises the extent to which educational leaders can forge effective partnerships that benefit students from the most alienated, disenfranchised and marginalized communities (e.g., Black children in under-resourced schools). While the educational discourse has included recommendations for maximizing interactions between these educational professionals, the collective voices of teachers, school counselors and administrators in regards to these issues has not been adequately examined. Thus, this book is a compilation of manuscripts and studies that explore partnerships and strategies educators and educational leaders use to produce positive socio-educational outcomes for Black students in various contexts. "Creating and Sustaining Effective K-12 School Partnerships: Firsthand Accounts of Promising Practices" is unique because it illuminates examples of effective school- community partnerships that foster positive student outcomes. "Creating and Sustaining Effective K-12 School Partnerships: Firsthand Accounts of Promising Practices" is intended as a practical text for committed educational leaders, at different professional points (e.g. practicing teachers, pre- service school counselors and teachers), who are eager to transform the current educational trajectory of Black children through interventions that show promise"--